Imigração no Brasil e na Alemanha: contextos, conceitos, convergências - Sérgio Costa (Ciências Sociais Unisinos, 2008)
The article compares discourses and policies directed to immigrants in Brazil during the "nationalization campaign" at the time of the Second World War with efforts to "integrate" immigrants in contemporary Germany. Looking beyond some historical and structural differences, the author identifies important similarities between these two contexts. In both cases immigrants are supposed to have a low identification with the "national values" and the State tries to correct this alleged deficit using disciplinary and/or assimilationistic measures.